A new Pristimantis (Anura, Strabomantidae) from Yuruani-tepui, Venezuela - Rödder, Dennis; Jungfer, Karl-Heinz (Zootaxa, 2008)
Pristimantis yuruaniensis sp. nov. is described from the summit of Yuruaní-tepui, Estado Bolívar, eastern Venezuela. The new species is easily distinguished from other Guianan Pristimantis by its rather uniform dorsal coloration, absence of lip, forearm and shank bars, its small tympanum, and its advertisement call. The new species appears to occur on neighboring Kukenán-tepui as well.